Turkey’s Contrıbutıon To The Graduate Theologıcal Studies In Kyrgyzstan - Gökalp, Yusuf; Kalmurza uulu, Ulanbek (Scientific Journal of Faculty of Theology, 2020)
In the post-independence period, there has been an intense co-operation between the Kyrgyz Republic and the Republic of Turkey in political, economic, social and cultural areas. In the post-independence period in Kyrgyzstan, a new process has started in the field of theology education. In order to share Turkey’s experience in the field of theology education and to mutual cooperation, academic studies have been given weight between the faculties of theology in both countries. In this context, it is seen that undergraduate students studying theology in Kyrgyzstan prefer Turkey for graduate education. In this study, it is aimed to analyze the students who go to Turkey for graduate education in terms of departments they prefer, the universities they study, the content of their work felds, their achievement rates, the organizations supporting their education and the types of scholarships they receive, the years of graduation and the distribution of outgoing students according to their gender etc. We believe that such a study is important in terms of seeing the current status of higher religious education in Kyrgyzstan and planning for the future. We have the expectation that this study will be a guide especially for the faculties of theology and institutions such as TDV, YTB and TİKA that support the studies and projects carried out in this field and for candidate academicians.